A study on a healthy workplace concept implementation - T.W, Han,; Hassan, C.R, Che; M.R, Osman, (Malaysian Journal of Science, 2004)
The notion of workplace health and well-being has evolved significantly in recent years. The holistic workplace health systems of today aim to provide support on many levels such as physical, social, personal and development in order to improve the overall employee quality of life both within and outside the workplace. As the world-leading organisation of health, the World Health Organisation (WHO) has come out with a guideline on Healthy Workplace (HWP). In Malaysia, the government is in the progress of evaluating and assessing the guideline with the intention of adopting it. This paper reports a survey conducted on the organisation implementing the healthy workplaces concept. The survey was conducted by interviewing members of the organisation based on the questionnaire recommended by WHO guidelines with some modifications to suit the organisation culture. The survey attempts to incorporate ISO 14000 Environmental Management System (EMS) into the implementation of this healthy workplace concept. The survey results reveal that ISO 14000 system is able to set a framework to implement healthy workplace concept provided the organisation has a strong commitment in the implementation.